A framework to accelerate simulation studies of hyperacute stroke systems. (December 2017) - Monks, Thomas; van der Zee, Durk-Jouke; Lahr, Maarten M.H.; Allen, Michael; Pearn, Kerry; James, Martin A.; Buskens, Erik; Luijckx, Gert-Jan
Abstract: Stroke care has been identified as an area where operations research has great potential. In recent years there has been a small but sustained stream of discrete-event simulation case studies in modelling hyperacute stroke systems. The nature of such case studies has led to a fragmented knowledge base and high entry cost to stroke modelling research. Two common issues have faced researchers in stroke care: understanding the logistics and clinical aspects of stroke care and moving from these findings to an appropriately detailed model. We aim to accelerate studies in this area by introducing a conceptual modelling framework that is domain specific for stroke. A domain specific framework trades-off the wide applicability of a general framework against increased efficiency and reuse to support modelling in the problem domain. This compromise is appropriate when the problem domain is complex, of high value to society, and where the saving in future modelling effort is likely to be greater than the effort to create the framework. We detail the requirements of a domain specific conceptual model and then provide domain specific knowledge to support modellers in gaining an understanding of the problem situation, translating this knowledge into selected model outputs, inputs and content in the case of hyperacute stroke. We illustrate the use of the framework with an example based at a large hospital in the United Kingdom. Highlights: We define a domain specific modelling framework for decision support in stroke. Domain specific frameworks improve reuse and efficiency of studies. We define the requirements for a domain specific conceptual modelling framework. We propose an extended framework for endovascular therapy. We illustrate the use of the framework with a real world example.